Analysis Of Factors Affecting The Speed Of Urban Public Transport In Andijan City (Texas Journal of Engineering and Technology, 2025)
A distinctive feature of urban public passenger transport is its organization of movement along certain routes (including route taxis). An important element in assessing passenger transport services is the selection of criteria for evaluating the effectiveness of the final results of the transportation process. This requires the use of logistics methods in organizing urban passenger transport.